MANAGING STRESS IN MODERN LIFE - Moh.Muslim (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
Modern life is characterized by information acceleration, complex work demands, seamless digital connectivity,Global uncertainty has increased the prevalence of stress in society. Stress, once considered an individual psychological disorder, has now become a collective phenomenon that threatens the quality of human life.Often, stress is hidden in everyday routines, so symptoms such as fatigue or anxietyoften ignored because it is considered normal, even though both are indicatorsimportant thatrequires a serious response. This article aims to raise awareness of the risks of stress by analyzing its indicators, variations in individual responses, and personality characteristics that influence how people cope. The solutions offered include conceptual and practical approaches, such as strengthening resilience through emotional intelligence, mindfulness techniques, social support, and effective time management. These strategies are designed to build resilience, enabling individuals to remain productive and maintain a balanced life amidst the dynamics of change and uncertainty. The paradigm shift in stress management now emphasizes a holistic approach focused on enhancing adaptive capacity. Its implementation involves self-awareness, long-term commitment, and collaboration with the surrounding environment to achieve well-being.